Effect of coronary artery disease severity and revascularization completeness on 2-year clinical outcomes in patients undergoing transcatether aortic valve replacement. Issue 7 (November 2015) - Witberg, Guy; Lavi, Ifat; Harari, Emmanuel; Shohat, Tzipora; Orvin, Katia; Codner, Pablo; Vaknin-Assa, Hana; Assali, Abid; Kornowski, Ran
<x xml:space="preserve">Abstract</x> Aims To evaluate the effect of coronary artery disease (CAD) severity and completeness of revascularization on clinical outcomes following transcatheter aortic valve replacement (TAVR) using the SYNTAX score (SS), clinical SYNTAX score (cSS), and residual SYNTAX score (rSS). Methods and results We studied 287 consecutive patients undergoing TAVR at our institution. Patients were classified as having CAD or no CAD and coronary patients were stratified according to SS and cSS. The completeness of revascularization was stratified using the rSS. We compared the 2-year outcomes according to SS/cSS/rSS. Forty-nine patients (17.1%) had CAD and sustained a higher rate of the primary endpoint at 2 years (28.3 vs. 16.1%, P=0.026). Stratified by CAD severity, the difference was driven by the high-severity groups (75.0 vs. 16.1%, P=0.002 for SS>22 and 41.2 vs. 16.1%, P=0.001 for cSS>63). Low-severity CAD patients did not have worse outcomes versus no CAD. When evaluating the effect of revascularization, patients with a rSS less than 8 did not have worse outcomes versus patients who did not have CAD. Conclusion In patients undergoing TAVR, it is the severity of CAD (as assessed by the SS/cSS) that is associated with worse prognosis and not the mere presence of CAD. More complete revascularization attenuates the effect of CAD on clinical outcomes.